2011
DOI: 10.1002/jbm.a.33221
|View full text |Cite
|
Sign up to set email alerts
|

Highly superporous cholesterol‐modified poly(2‐hydroxyethyl methacrylate) scaffolds for spinal cord injury repair

Abstract: Modifications of poly(2-hydroxyethyl methacrylate) (PHEMA) with cholesterol and the introduction of large pores have been developed to create highly superporous hydrogels that promote cell-surface interactions and that can serve as a permissive scaffold for spinal cord injury (SCI) treatment. Highly superporous cholesterol-modified PHEMA scaffolds have been prepared by the bulk radical copolymerization of 2-hydroxyethyl methacrylate (HEMA), cholesterol methacrylate (CHLMA), and ethylene dimethacrylate (EDMA) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 46 publications
0
47
0
Order By: Relevance
“…32 In comparison with the synthetic nondegradable materials based on poly(2-hydroxyethyl methacrylate), which we previously developed and evaluated in vivo, 33,34 ECM hydrogels are undoubtedly advantageous, in terms of their injectability, degradability, as well as their biological activity, which is able to modulate the immune response and stimulate vascularization and axonal ingrowth. At the same time, there are also two impediments that hinder the use of ECM hydrogels in their current form as optimal materials for CNS repair: (1) progressive hydrogel contraction in combination with fibroblast-like cells, such as MSCs and (2) rapid in vivo hydrogel degradation, which was too fast to be followed by full tissue reconstruction in the lesion cavity.…”
Section: Discussionmentioning
confidence: 99%
“…32 In comparison with the synthetic nondegradable materials based on poly(2-hydroxyethyl methacrylate), which we previously developed and evaluated in vivo, 33,34 ECM hydrogels are undoubtedly advantageous, in terms of their injectability, degradability, as well as their biological activity, which is able to modulate the immune response and stimulate vascularization and axonal ingrowth. At the same time, there are also two impediments that hinder the use of ECM hydrogels in their current form as optimal materials for CNS repair: (1) progressive hydrogel contraction in combination with fibroblast-like cells, such as MSCs and (2) rapid in vivo hydrogel degradation, which was too fast to be followed by full tissue reconstruction in the lesion cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Factors affecting cell adhesion to a polymer surface include the chemical composition, the net charge of the surface, and the balance between hydrophilic and hydrophobic micro-domains. To improve the biocompatibility of PHEMA scaffolds, the introduction of groups with positive charges [111] or modification with cholesterol [112,113] has been studied. Modifying the surface of PHEMA-based hydrogels with different surface charges showed that, after implantation into the hemisected spinal cord, hydrogels with positively charged functional groups promoted connective tissue infiltration and extended axonal ingrowth into the hydrogel bridge, compared to negatively or uncharged hydrogels [111].…”
Section: Biomaterial-based Matrices For Spinal Cord Injury Repairmentioning
confidence: 99%
“…Some non‐degradable materials composed of synthetic polymethacrylates have shown notable success as implants due to their stiffness without causing compression of the SC tissue . This feature makes non‐degradable materials favorable to cell encapsulation and to providing the proper 3D networks for bridging neural tissues …”
Section: Introductionmentioning
confidence: 99%